HIV prevalence, risk factors, prevention methods, and interventions among taxi drivers and commercial motorcyclists in sub-Saharan Africa: A scoping review. - John Baptist Asiimwe; Benjamin Betunga; Lilian Birungi; Joy Kabasindi Kamanyire; Moses Wankiiri; Lilian Nuwabaine; Joseph Kawuki; Edward Kumakech (PLOS Global Public Health)
Transport workers, particularly taxi drivers and commercial motorcyclists, comprise a population at high risk for HIV and account for nearly one-third of new HIV infections in sub-Saharan Africa (SSA). Transport workers bridge HIV infections from high-risk populations to the general population. This scoping review aimed to map the available evidence around HIV prevalence, risk factors, prevention methods, and interventions among taxi drivers and commercial motorcyclists in SSA. This scoping review used the Arksey and O'Malley framework. Published articles were retrieved from MEDLINE, CINAHL, African Index Medicus, Web of Science, Scopus, EMBASE, HINARI, and Google Scholar from January 2000 to August 2024. Two authors screened the titles and abstracts of retrieved studies and examined the references of relevant articles for additional literature. Three authors independently extracted data from the included studies using a standard data extraction form. Data were analyzed using descriptive statistics and content analysis techniques. This review included 24 out of 126 studies. The HIV prevalence was 2.02%-9.9% among commercial motorcyclists and reached 33.4% in samples comprising both motorcyclists and taxi drivers. The high HIV infection rate in SSA when compared with the global adult general population was associated with numerous behavioral (e.g., multiple sex partners), psychosocial (e.g., stigma), and sociodemographic (e.g., age) risk factors. However, there was suboptimal use of HIV prevention methods such as safe male circumcision (20.7%-64.9%) and condoms (26%-45.7%) and few interventional studies (n = 2). Despite HIV testing being an entry point for chronic care, we found no study reporting the HIV cascade for commercial motorcyclists or taxi drivers with HIV. To inform better HIV policies and programs in SSA this review recommends additional observational and interventional research on HIV incidence, predictors, new models of HIV testing, antiretroviral-based HIV prevention methods, and the role of peer-to-peer support models in reducing HIV infection.